Proceedings of the 21st Annual International Conference on Supercomputing 2007
DOI: 10.1145/1274971.1275006
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost mixed-mode parallel processor architecture for embedded systems

Abstract: A scalable SIMD/MIMD mixed-mode parallel processor architecture called XC core is proposed to meet the high and diverse performance requirements of embedded multimedia applications. XC core supports both the SIMD and MIMD computing models at low hardware cost by dynamically reconfiguring itself into datapath circuits or control circuits, i.e., trading off between performance and flexibility. A control processor is used to broadcast instructions to a whole SIMD PE (Processing Element) array or to a part of it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…By reusing the hardware of four PEs in these ways, the additional hardware costs for implementing the MIMD mode, including the costs for the ROI transfer instructions described in Section 2.2, have been kept to approximately 10% of the costs for the whole XC core 6) .…”
Section: Basic Structures Of the XC Corementioning
confidence: 99%
See 1 more Smart Citation
“…By reusing the hardware of four PEs in these ways, the additional hardware costs for implementing the MIMD mode, including the costs for the ROI transfer instructions described in Section 2.2, have been kept to approximately 10% of the costs for the whole XC core 6) .…”
Section: Basic Structures Of the XC Corementioning
confidence: 99%
“…To solve these issues, we have designed a processor architecture called the XC core, which can dynamically switch between the SIMD and MIMD modes 6) . In addition to the conventional SIMD mode, the XC core also implements a MIMD mode in which four PEs are reconfigured as one operation unit (PU: Processing Unit), as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such direction of evolution will enhance the versatility of vision processors, however, the strict cost limitation coming from the product side and the performance and flexibility requirements coming from the vision application side will drive such research activities, whereby the architectural design approaches for vision processors will be differentiated from those for more general-purpose oriented future multi-or many-core processor design approaches. One research activity toward this challenge can be found in [8], where a novel hardware component reuse design methodology is proposed to support task level parallelism through low-cost dynamic reconfiguration of a pure highly parallel SIMD architecture.…”
Section: Technology Perspective Of Next Generation In-vehicle Vision mentioning
confidence: 99%